Association of Atherogenic Index and Oxidized-LDL as a Strong Independent Risk Predictor of CHD in Young Smokers - Shivasekar, Meera; Nath, Dinesh; Vinodhini, V. M. (Research Highlights in Disease and Health Research Vol. 7, 2023)
Introduction: cigarette smoking is an environmental risk factor for cardiovascular disease and induces changes in lipid profile by the oxidation of lipids, particularly LDL. Hence the need for determine ox-LDL and its association with atherogenic indices in the risk of cardiovascular risk. The study aimed to determine oxidized-LDL and atherogenic indices in relation to cigarette smokers Methods: This case-control study included 240 individuals in which cigarette smokers were (n=120) and were compared with (n=120) non-smokers. The ox-LDL, APO-A1, and APO-B were performed using Enzyme-linked Immune Sorbent Assay (ELISA) and atherogenic risk ratios were calculated. Results: The study shows that ox-LDL was a significantly increased in smokers and also significant increase in TC, TGL, and LDL was observed. When compared to nonsmokers, smokers had considerably higher atherogenic risk indices. Pearson correlation tests revealed that ox-LDL and AIP were substantially and positively linked with non-HDL, CRI- Castelli's risk Index-I, CRII- Castelli's risk Index-II, AC-Atherogenic Coefficient, CI-Cholindex, and APO-B- Apolipoprotein B (p<0.001). And was inversely associated with APO-A1 and HDL-C (p<0.001). The unadjusted odds ratios for ox-LDL and AIP in the univariate logistic regression analysis were 1.861 (95% confidence interval: 1.347-2.375), p<0.001, and 1.782 (95% confidence interval: 1.490-2.131), P.001), respectively. Multivariate logistic regression analysis demonstrated that ox-LDL and AIP were independent risk factors for CHD in young smokers. Conclusion: In smokers, ox-LDL and atherogenic indices appear to be strong independent risk predictors for CHD than conventional lipid parameters.